2019
DOI: 10.1016/j.jhsg.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Supraretinacular Endoscopic Carpal Tunnel Release: Instrumentation and Technique (Cadaveric Study)

Abstract: Purpose: Endoscopic carpal tunnel release has been shown to be associated with a shorter return to work compared with open carpal tunnel release in the treatment of carpal tunnel syndrome. Unfortunately, it may be associated with a higher risk for median nerve injury when the carpal tunnel is used as a portal for instrumentation. The purpose of this study was to assess safety in using a newly designed retractor through a supraretinacular approach. Methods: We used 8 wrists (4 left and 4 right wrists) from 4 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Previously, we designed a smaller instrumentation and a technique to release the transverse carpal ligament through a similar approach. 7 In that study, we described a new technique using the supraretinacular approach and found that by abiding to a safe zone, we could perform ECTR without causing any injuries to vital structures in the wrist—namely, the median nerve, superficial palmar arch, and flexor tendons—or violation of the Guyon canal.…”
mentioning
confidence: 99%
“…Previously, we designed a smaller instrumentation and a technique to release the transverse carpal ligament through a similar approach. 7 In that study, we described a new technique using the supraretinacular approach and found that by abiding to a safe zone, we could perform ECTR without causing any injuries to vital structures in the wrist—namely, the median nerve, superficial palmar arch, and flexor tendons—or violation of the Guyon canal.…”
mentioning
confidence: 99%
“…No obstante, estos procedimientos endoscópicos pueden generar eventuales lesiones neurológicas en caso de variantes anatómicas, así como dañar mecanorreceptores en la región palmar de la muñeca, por lo que no parecen representar una alternativa superior frente a las vigentes técnicas infrarretinaculares. [30][31][32] conclusIones La retinaculotomía endoscópica del túnel carpiano mediante la técnica de dos portales de Chow es una intervención quirúrgica reglada, eficaz y segura para el tratamiento del STC. La tasa de complicaciones es mínima cuando la intervención está en manos de un equipo quirúrgico cohesionado, liderado por un primer cirujano experimentado.…”
Section: Discussionunclassified
“…Another critical aspect is the need to insert devices into the CT, thereby increasing the pressure on the median nerve, already damaged from chronic compression. Supraretinacular approaches, as proposed by some authors,16–19 would prevent such transient deficit of nerve function, but the use of relatively bulky devices may disrupt the subtle volar anatomy more than necessary and contribute to higher incidence of pillar pain.…”
mentioning
confidence: 99%